The Perkembangan Visualisasi Ilustrasi Cerita Pendek Majalah Bobo Tahun 1975-1985: Perkembangan Visualisasi Ilustrasi Cerita Pendek Majalah Bobo Tahun 1975-1985 - Muryanto, Nathalia Andita (Wimba : Jurnal Komunikasi Visual, 2025)
Bobo Magazine is one of the popular children's readings that remains popular to this day. Bobo Magazine was first published in 1973 during the New Order era. From 1975 to 1985, book publishing in Indonesia experienced rapid growth due to national development, and during that time, there were advancements in the visualization of illustrations in Bobo Magazine's short stories.This study aims to determine the factors that contribute to the development of illustration visualization in Bobo Magazine. The data used consists of documentation of Bobo Magazine's short story illustrations from 1975 to 1985. The obtained data was then observed and reviewed through literature studies to identify the factors that caused the advancement of illustrations during that period, including both social factors and technological advancements that contributed to the progress of illustration in Indonesia